Twitter Data Analysis on Halal Labeling: Insights for the Food Industry in Indonesia - Izza, Nadia Nurul; Fitria, Lia; Arsyi, Muhammad; Nugraha, Fajar (Halal Tourism and Pilgrimage, 2023)
This research uses text data mining techniques and the Drone Emprit Academic (DEA) system to identify and collect current problems related to the Halal label. The data analyzed includes 2,665 conversations from August 19, 2022 to March 15, 2023. The results show that conversations around the Halal label are closely related to the popular food franchise industry, with words such as "gacoan," "food," and "mixue" appearing the most frequently. In addition, this research found that sentiment towards the halal label varied, with 52% positive sentiment, 44% negative sentiment, and 3% neutral sentiment. Interestingly, in this finding, the initial discussion regarding Gacoan and Mixue which had a negative sentiment then turned positive after they both obtained halal certification and displayed the halal logo on their products. Thus, the implications of this research can contribute to further understanding of social media data analysis related to Halal labels in the food industry in Indonesia as well as increasing insight and thinking regarding this issue, and offering further research directions.